Kemampuan Alat Penyaring Udara Dengan Media Pelepah Pisang dan Zeolite untuk Menurunkan Kadar Karbon Monoksida(Co) di Udara - ST. Mu`tamirah (Journal of Mandalika Literature, 2024)
The research method used is the experimental method. The population in this study are all points or locations that produce air pollutants (CO) in the process of transporting vehicle exhaust gases taken around red lights. The sampling technique was a non-randomized pretest-posttest control design, namely the objects used consisted of two groups. The first group is an experimental unit for measuring CO emissions before passing through the filter device and the second group is a control group for exchange after passing through the filter device. The results of the research can be concluded that: The carbon monoxide (CO) level before passing through the banana stem and zeolite filter media is 60 ppm at the point first and 700 ppm at the second point. The results of reducing CO levels using a banana peel air filter and zeolite were 66.6% at point 1 and 84% at point 2. The thing that caused the difference in measurement results at these two points was the different object placement of the equipment, at point 1 the measurement was carried out far from the CO source (vehicle) and at point 2 the measurements are carried out directly at the exhaust of the motor vehicle. Future researchers should design a tool that is easy to carry anywhere, so that it is not difficult to lift it during research. It is recommended that this research should be carried out indoors, such as a basement, so that the CO measurement results produced are quite accurate. Considering that there are many materials that can be used as air filters, it is necessary to carry out research on different media that may be more effective and efficient. Apart from that, differences in contact time and the amount of media used must be taken into account in terms of effectiveness.